The students’ learning experience of using digital storybook at junior high school - Al Zahra, Salsabilla; Aisyah; Maisa (Research and Innovation in Language Learning, 2025)
Reading comprehension is one of the biggest challenges students face in public schools, and it is thought that reading fluency problems can be caused by a lack of reading practice. This research article reports qualitative research that explores student collaboration through English reading practice using digital storybooks. This research was conducted with 22 junior high school students in Cirebon. The results of qualitative data collected through questionnaires, interviews, and classroom observations were analyzed using thematic analysis. The results show that students prefer learning using digital media because that way they can understand learning using digital media well, thereby giving rise to the experience they experience. Apart from that, working using digital media can improve skills and provide a good understanding and train students' focus so that students can read fluently. Thus, skill in reading can develop students' vocabulary knowledge process in reading positively, so that they are bolder in expressing themselves as they can read well.